Mengelola Hidup Bahagia bagi Mahasiswa: Managing Happy Life for Students - Rianto, Puji; Nashori, Fuad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Today, many young people are less able to manage their lives to are unhappy, such as insomnia, anxiety, stress, depression, addiction to drugs or alcohol, and problematic emotional relationships. This problem is becoming more severe due to the widespread use of social media. Although social media provides easy and inexpensive communication facilities, it also creates vulnerability for young people due to the flood of communications and hoaxes. This situation is unfavorable for young people, so it needs